A Method to Transit the Rotor-to-Stator Rubbing to Normal Motion Using the Phase Characteristic - Jieqiong Xu; Qunhong Li; Shimin Wang (Discrete Dynamics in Nature and Society)
A method is proposed to transit the rotor-to-stator rubbing to no-rub motion through active auxiliary bearing. The key point of this technique is to express the attractive domain of no-rub motion based on the phase characteristic and to represent the desired status. The feedback actuation is applied by an active auxiliary bearing to drive the rotor approaching the desired status. After that, the control actuation is turned off. Although the desired status is still in rubbing, it is in the attractive domain of no-rub motion, and the response of the rotor is automatically attracted to no-rub motion.